Numerical analysis of the alanine response using Monte Carlo: Correlation with experimental results. (January 2022) - Rouihem, F.; Hosni, F.; Dridi, W.; Daoudi, M.; Blaise, P.; Bignan, G.; Farah, K.
Abstract: International centers based on research reactors (ICERR) project supported by IAEA, offers training and research in the application of advanced nuclear reactor technology. In this context of the project, alanine dosimeters were irradiated under mixed neutron/gamma irradiation in the core of the MINERVE research reactor at the CEA Cadarache. The integrated dose of the alanine was measured by electron spin resonance spectrometry with reference to an absorbed dose in water from a 60 Co gamma-ray beam. Neutron and gamma dose components were calculated using the MCNP code. The neutron dose and relative effectiveness ( R E n ) for neutrons was evaluated using FLUKA code and Track Structure Theory (TST) formulations of alanine response towards irradiations with ions produced by neutron interactions with alanine. R E n values were found to be between 0.516 and 0.538. The measured dose was compared to the calculation results. The best agreement between the alanine integral measurements and model predictions (0.4%) was obtained by using the Cucinotta alanine detector response model. Highlights: Integrated dose at CEA Minerve reactor core was measured using alanine dosimeters. Neutron and gamma dose components were calculated using the MCNP code. Energy spectra of ions generated by neutrons were calculated by the FLUKA code. R E n values were calculated from a combination of the energy spectra and RE of ions. The measured dose of the alanine was evaluated and compared to model predictions.